A Study of Racial Discrimination in Countee Cullen's Selected Poems - Rahmawati, Santi (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
This research aims to analyze racial discrimination issues in three poems written by Countee Cullen: “Tableau” (1920), “Incident” (1925), and “From the Dark Tower” (1927). Racial discrimination is part of reality that still happens in society. This reality is adapted into works of literature and poem is one of the branches of literature. Countee Cullen is one of the well-known poets of the Harlem Renaissance era. There are several poems by Countee Cullen that depicted racial discrimination which is still in line with the issues nowadays. The research method of this research is qualitative research. Racial discrimination that has been portrayed in Countee Cullen’s three poems has been proofed that the related issues are still happening in society nowadays. The issues that are related to the three poems such as Interracial Married Couples, Racial Slur, “the N-word”, the Black Lives Matter Movement, and Equal Pay Equal Work for Black Women. These related issued are in correlation with Theodorson and Theodorson’s theory of discrimination. These data have been supported by online news that is happened in the United States.